Campur Kode dalam Acara Rapat Desa pada Penutur Bahasa Bajau di Desa Pulau Bungin Kecamatan Alas Kabupaten Sumbawa - Erwinsyah Putra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research answers the problem of code mixing in village meeting events for language speakers in Pulau Bungin Village, Alas District, Sumbawa Regency. The method used in this research is descriptive qualitative method. The data were analyzed using an ethnographic approach to communication or speech components during speech events. The speech component consists of the place where the speech event takes place; speech participant; speaking purpose; form and topic of speech; tone in speech; means of speaking; norms of speech and types of speech. The stage of providing research data begins with observation, interview techniques, and recording techniques. Furthermore, the listening method is used, using tapping techniques, engaging listening techniques, note-taking techniques in the form of phonetic transcriptions, and transliteration techniques. Data validity uses triangulation techniques. The data analysis phase uses an interactive analysis model. This study concludes that the code mixing that occurred in the Bajau-speaking village meeting event in Pulau Bungin Village, Alas District, Sumbawa Regency consisted of internal code mixing and external code mixing. The form of code mixing in village meeting events is the insertion of lingual units of Bajau words, phrases and clauses into Indonesian. This means that Indonesian is the basic language for code mixing. Meanwhile, external code mixing only involves Indonesian and English. The form of code-mixing that is heard in the speech of Bajau speakers is the insertion of lingual units of English clauses into Indonesian.